A virtual art festival in West Java; Participatory culture during the pandemic - Lahpan, Neneng Yanti Khozanatu (UI Scholars Hub, 2025)
YouTube was used as a significant platform for public performances around the globe during the COVID-19 pandemic, including those given by contemporary and traditional artists and communities. Although this transference of public performance to virtual performance has meant challenges for traditional artists, it has also encouraged them to create new creative media spaces. Instead of confronting digital technology, some traditional artists compromise and negotiate with it. Through an ethnographic account of a performance in Tasikmalaya, West Java, this article describes how traditional artistic forms were preserved through a virtual-based art festival performed by the art community, Komunitas Cermin Tasikmalaya. Solidarity, collaboration, and networking were crucial elements in holding the online festival in which young people were the main actors in this participatory culture, which was widely disseminated through YouTube.